THE MATHEMATICAL MODELING OF TUNNEL KILN - Irina Gennadyevna Afanasyeva (Современная наука и инновации, 2022)
The paper attempts to create a fairly simple model requiring reasonable machine time and costs and, at the same time, allowing to use it for the synthesis of thermal management systems and to analyze the temperature fields in different zones of the furnace.